Pharmacological and pharmacokinetic properties of JNJ‐40411813, a positive allosteric modulator of the mGlu2 receptor. Issue 1 (9th December 2014) - Lavreysen, Hilde; Ahnaou, Abdellah; Drinkenburg, Wilhelmus; Langlois, Xavier; Mackie, Claire; Pype, Stefan; Lütjens, Robert; Le Poul, Emmanuel; Trabanco, Andrés A.; Nuñez, José María Cid
Abstract Compounds modulating metabotropic glutamate type 2 (mGlu2) receptor activity may have therapeutic benefits in treating psychiatric disorders like schizophrenia and anxiety. The pharmacological and pharmacokinetic properties of a novel mGlu2 receptor‐positive allosteric modulator (PAM), 1‐butyl‐3‐chloro‐4‐(4‐phenyl‐1‐piperidinyl)‐2(1H)‐pyridinone (JNJ‐40411813/ADX71149) are described here. JNJ‐40411813 acts as a PAM at the cloned mGlu2 receptor: EC50 = 147 ± 42 nmol/L in a [35S]GTPγS binding assay with human metabotropic glutamate type 2 (hmGlu2) CHO cells and EC50 = 64 ± 29 nmol/L in a Ca2+ mobilization assay with hmGlu2 Gα16 cotransfected HEK293 cells. [35S]GTPγS autoradiography on rat brain slices confirmed PAM activity of JNJ‐40411813 on native mGlu2 receptor. JNJ‐40411813 displaced [3H]JNJ‐40068782 and [3H]JNJ‐46281222 (mGlu2 receptor PAMs), while it failed to displace [3H]LY341495 (a competitive mGlu2/3 receptor antagonist). In rats, JNJ‐40411813 showed ex vivo mGlu2 receptor occupancy using [3H]JNJ‐46281222 with ED50 of 16 mg/kg (p.o.). PK‐PD modeling using the same radioligand resulted in an EC50 of 1032 ng/mL. While JNJ‐40411813 demonstrated moderate affinity for human 5HT2A receptor in vitro (Kb = 1.1 μmol/L), higher than expected 5HT2A occupancy was observed in vivo (in rats, ED50 = 17 mg/kg p.o.) due to a metabolite. JNJ‐40411813 dose dependently suppressed REM sleep (LAD, 3 mg/kg p.o.), and promoted and consolidated deep sleep. In fed rats, JNJ‐40411813 (10 mg/kg p.o.) was rapidly absorbed (Cmax 938 ng/mL at 0.5 h) with an absolute oral bioavailability of 31%. Collectively, our data show that JNJ‐40411813 is an interesting candidate to explore the therapeutic potential of mGlu2 PAMs, in in vivo rodents experiments as well as in clinical studies.